2021
DOI: 10.3390/pathogens10020217
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine and Hydroxychloroquine: Efficacy in the Treatment of the COVID-19

Abstract: Chloroquine (CQ) and its derivative, hydroxychloroquine (HCQ), have attracted wide attention for treating coronavirus disease 2019 (COVID-19). However, conflicting outcomes have been found in COVID-19 clinical trials after treatment with CQ or HCQ. To date, it remains uncertain whether CQ and HCQ are beneficial antiviral drugs for combating COVID-19. We performed a systematic review to depict the efficacy of CQ or HCQ for the treatment of COVID-19. The guidelines of PRISMA were used to conduct this systematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…Inhibition of MASP-2 using HG4 significantly impairs complement C3b deposition on the surface of HEK 293T cells expressing S protein. Many other complement inhibitors and anti-inflammatory drugs have been re-purposed and evaluated in COVID-19 clinical trials but, to date, none of those other agents have yielded a breakthrough in the treatment of severe COVID-19 (22)(23)(24)(25)(26)(27). While vaccination is reducing hospitalisation, there is a fear of possible reduction in the efficacy against the new variants, which are responsible for severe cases of COVID-19 in younger age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of MASP-2 using HG4 significantly impairs complement C3b deposition on the surface of HEK 293T cells expressing S protein. Many other complement inhibitors and anti-inflammatory drugs have been re-purposed and evaluated in COVID-19 clinical trials but, to date, none of those other agents have yielded a breakthrough in the treatment of severe COVID-19 (22)(23)(24)(25)(26)(27). While vaccination is reducing hospitalisation, there is a fear of possible reduction in the efficacy against the new variants, which are responsible for severe cases of COVID-19 in younger age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show that CQ is not effective in treating patients with severe COVID-19. Moreover, it causes serious side effects, which may cause potential cardiac toxicity in patients with severe COVID-19 [ 138 ].…”
Section: Viral Infection and Autophagymentioning
confidence: 99%
“…At the onset of the pandemic, chloroquine and hydroxychloroquine with or without antibiotics, including azithromycin were recommended. Subsequent investigations demonstrated that these agents do not affect mortality (7)(8)(9)(10). Meanwhile, the effect of remdesivir was indicated to be different in variable studies (11,12).…”
Section: Introductionmentioning
confidence: 99%